History of the theological method of Reinhold Niebuhr : a study of the relationship between past and contemporary events in Niebuhr's theological method - Leatt, James (Department of Religious Studies, 2016)
Reinhold Niebuhr is widely acknowledged, by religious and secular opinion alike, as the most influential Christian social ethicist of the twentieth century. For over fifty years he grappled with the issues which confronted his native America at a time when that nation was undergoing the most dramatic period of change in its history. During this time there was considerable debate about method in Christian ethics, but with little or no success. By contrast Niebuhr hardly seems to have a method, but perhaps behind his considerable success lies hidden a method which must be made explicit for the contemporary debate in Christian ethics. Since we have summarized our argument at the beginning of each chapter, it is necessary here only to indicate the main outline of this thesis. The contemporary debate in Christian ethics forms the subject of our first chapter, and states the problem with which this work is concerned. We then examine the formative context of Reinhold Niebuhr's life and work, before giving an exposition and critique of his Christian realism. The last two chapters seek to elucidate the theological method of Reinhold Niebuhr, and to offer an evaluation and critique.